Folk songs and the regional geographic environment: the influence and inspiration of biodiversity and ecosystems on Chinese folk songs in the Yangtze River Delta - Chenyu Wang; Qing Chang; Yizheng Liu; Pengcheng Wang; Yihong Zhan (Humanities & Social Sciences Communications)
Abstract The geographical environment forms the foundation for human existence and cultural development and serves as a vital source of inspiration within cultural ecosystem services (CES). In China, numerous folk songs reference ecosystems and biodiversity, providing a unique data source to quantify the inspirational impacts of these songs. This study examines the relationship between folk songs and the regional geographic environment and evaluates how ecosystems and biodiversity inspire the creation of folk songs on the basis of Chinese folk songs from the Yangtze River Delta region. The species names and ecosystem types referenced in the lyrics to 4072 Chinese folk songs were studied, categorized into distinct groups, and examined with multiple regression analysis. Among the analyzed songs, 52.58% referenced biodiversity and 19.43% mentioned specific ecosystems. The most prevalent ecosystems mentioned were wetlands and farmlands, whereas plants, mammals, and birds were the most commonly mentioned taxonomic groups. The primary sources of inspiration included the plant families Rosaceae, Poaceae, and Nelumbonaceae, and the animal families Bombycidae, Cyprinidae, Anatidae, and Phasianidae, all of which are closely related to the lives of the local populace. The degree to which biodiversity and ecosystems impact folk songs varies across different regions. These findings underscore the crucial role of wildlife in inspiring Chinese folk songs and reveal the profound connection between these songs and the unique geography and local culture of the Yangtze River Delta region.